Penerapan Media Mind Mapping dalam Pembelajaran Untuk Meningkatkan Kemampuan Komunikasi Antarpribadi Mahasiswa - Bujuna Alhadad; Andi Agustan Arifin; Rizmada Azzahra (ILIN Institute, 2020)
The purpose of this research was to determine the application of Mind Mapping media in learning to improve interpersonal communication skills of students in the PGPAUD FKIP UNKHAIR study program. This research used the classroom action research. There are 30 people. The design of the research stage includes planning, action or implementation, observation and reflection. The data collection techniques used are observation and questionnaire. The data analysis technique in this research is descriptive analysis based on the result of observations and questionnaires. The result obtained are that the Mind Mapping technique can improve students’ interpersonal communication skills, this is shown by increasing interpersonal communication skills in each cycle The average value in the first cycle was 67.75% and the average value in the second cycle was 87.25%